PERNIKAHAN ANAK DI BAWAH UMUR DALAM PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Fadel, Fadel Muhammad; Khairul Musthafa, Muhammad; Johari; Akbarizan (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
In Islamic teachings, marriage is a form of worship carried out by a man and a woman through a contract with the aim of achieving a life of Sakinah, Mawaddah, and Warahmah. The regulations regarding marriage are contained in Law No. 1 of 1974 concerning Marriage Chapter 2 article 7 paragraph 1. This study aims to discuss Early Marriage in the Islamic Perspective and the Marriage Law. In this study, the authors used a qualitative research method. Based on the discussion, it can be concluded that Positive Law, such as the Marriage Law, comes from material law, namely factors that help form law or places where legal material is taken, such as norms, traditions, and habits. Then, Islamic law comes from the Qur'an and hadith, which are then interpreted by several scholars who have studied their knowledge in determining a law.